Pelatihan Pembuatan Wedang Uwuh sebagai Upaya Pemberdayaan UMKM Berbasis Herbal di Desa Wates, Kabupaten Kediri - Faizatul Fitria; Prima Agusti Lukis; Farida Noor Arifah; Fawait Afnani (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This community service program aimed to enhance the knowledge and skills of residents in Wates Village, Kediri Regency, in processing traditional herbal beverages, specifically wedang uwuh, as an effort to empower local micro, small, and medium enterprises (MSMEs). Wedang uwuh is a traditional Javanese drink made from a mixture of spices such as ginger, cloves, cinnamon, secang wood, pandan leaves, and rock sugar, which not only carries cultural value but also contains bioactive compounds such as flavonoids and phenolics that act as antioxidants. The potential of Wates Village as a herbal center, supported by its jamu tradition and diverse MSMEs, provided the foundation for this training program. Methods included initial observation, coordination with village officials and student volunteers, counseling on the health benefits of herbal ingredients, demonstration of hygienic preparation techniques, and training in packaging and labeling products. Evaluation was conducted through pretests and posttests with 27 participants to measure improvements in knowledge and skills. Results showed an increase in average scores from 56.30 to 59.26, although not statistically significant, while qualitative observations indicated greater confidence and interest among participants in developing herbal beverage businesses independently. This training had a positive impact on community understanding, skills, and motivation, serving as an initial step toward establishing herbal-based MSMEs in Wates Village.